Design of a rule based monetary policy in a Central Bank Digital Currency System - Jacob Wijngaard; Kees van Hee (The Central European Review of Economics and Management (CEREM), 2021)
Aim: This paper presupposes a purely Central Bank Digital Currency (CBDC) based system. Its aim is to describe how such a system facilitates complete new possibilities to design a suitable monetary policy. More specifically, the purpose is to show that the available monetary tools can be used to design a rule-based monetary policy that guarantees stability of purchasing power and interest rates. Research methods: The paper is design oriented. It describes how the monetary system could function The important monetary variables are defined and their relationship is described. To illustrate these variables and their relationship, simulation results of their behavior are added. Conclusions: It is shown that it is indeed possible to design a monetary policy that is rule based and guarantees stability of purchasing power and interest rates. Crucial elements in the design are linking the balances of the CBDC-accounts to a proxy of the domestic product and replacing the use of government bonds by allowing the government to borrow from the Central Bank and giving households and businesses the opportunity to open a savings account at the Central Bank. Originality: The approach is completely new. It is the result of rethinking the possibilities of a complete transition of bank money to CBDC. Implications: The paper shows that a more absolute transition to the use of CBDC makes it possible to establish a clearer and more stable monetary practice, and that it is necessary therefore to revise monetary theory.
Keywords: E42; E43; E52; E58; E63; 330; Design; CBDC; Rule-based; Monetary policy; Inflation correction; Domestic product proxy